Fundamentals of financial instruments : an introduction to stocks, bonds, foreign exchange, and derivatives - Parameswaran, Sunil K., 1964- (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2011)
Fundamentals of Financial Instruments deals with the global financial markets and the instruments that are traded in them. Most books on Finance tend to be heavily mathematical, which is perhaps inevitable given the technical nature of the subject. A few which attempt to cover the basics often end up with a very superficial exposition due to the authors' desire to avoid technicalities. This book emphasizes the concepts in a sequential logical fashion. At the relevant stages adequate mathematical representations are introduced. The objective is to ensure that the reader gets conceptual clarity reinforced by just the right level of technicalities to ensure a comprehensive exposure.
An Introduction to Financial Institutions, Instruments, and Markets -- Mathematics of Finance -- Equity Shares, Preferred Shares, and Stock Market Indexes -- Bonds -- Money Markets -- Forward and Futures Contracts -- Options Contracts -- Foreign Exchange -- Mortgages and Mortgage-Backed Securities -- Swaps -- Partial Derivative of the Price with Respect to the Yield -- Appendix 2.
Includes index.
Includes bibliographical references (pages 537-542) and index.
Print version record.
Keywords: Investments; Investments; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investments; Electronic books